A "layer-by-layer" building strategy for the fabrication of a metal–hydrogel–metallic nanoarray plasmonic cavity with dynamic color display performance. Issue 6 (25th January 2023) - Chen, Dan; Liu, Jiazhen; Ye, Shunsheng; Zhang, Xuemin; Zhang, Liying; Fan, Fuqiang; Wang, Tieqiang; Fu, Yu; Hu, Jianshe
Abstract : An innovative "layer-by-layer" building strategy is demonstrated to prepare a responsive polymer based metal–insulator–metallic nanoarray (MIMn) for dynamic plasmonic color displays. Abstract : Dynamic plasmonic color displays have been proposed as an outstanding candidate for the next generation of color displays due to their ultrahigh resolution and tunable optical color display performance. Herein, we propose an effective indirect "layer-by-layer" (LBL) building strategy for the fabrication of a responsive metal–insulator–metallic nanoarray (MIMn) cavity with dynamic plasmonic color display performance. The responsive MIMn cavity is constructed through preparing a bottom metal layer, a middle pH-responsive hydrogel layer, and a top metallic array subsequently based on a film preparation technique and nanostructure transfer technique. By controlling the structural parameters of the middle hydrogel layer, the plasmonic color of the as-prepared MIMn cavity can be well-tuned. What is more, owing to the pH-responsiveness of the middle hydrogel layer, the as-prepared MIMn cavity shows dynamic color display performance with facile controllability and good reproducibility. The proposed "layer-by-layer" building strategy not only preserves the structure and responsiveness of the middle hydrogel, but also realizes the precise control of the top metallic array. Together with the excellent dynamic features of the as-prepared MIMn cavity, it is believed that the proposed "layer-by-layer" building strategy will pave a new way to fabricate dynamic plasmonic color display materials for various application fields such as optical sensors, display devices, and activity monitors.